PAM-altering SNP-based allele-specific CRISPR-Cas9 therapeutic strategies for Huntington’s disease - Shin, Jun Wan; Hong, Eun Pyo; Park, Seri S.; Choi, Doo Eun; Zeng, Sophia; Chen, Richard Z.; Lee, Jong-Min (Molecular therapy. Methods & clinical development, 2022)
Huntington’s disease (HD) is caused by an expanded CAG repeat in huntingtin (HTT). Since HD is dominant and loss of HTT leads to neurological abnormalities, safe therapeutic strategies require selective inactivation of mutant HTT. Previously, we proposed a concept of CRISPR-Cas9 using mutant-specific PAM sites generated by SNPs to selectively inactivate mutant HTT. Aiming at revealing suitable targets for clinical development, we analyzed the largest HD genotype dataset to identify target PAM-altering SNPs (PAS) and subsequently evaluated their allele specificities. The gRNAs based on the PAM sites generated by rs2857935, rs16843804, and rs16843836 showed high levels of allele specificity in patient-derived cells. Simultaneous use of two gRNAs based on rs2857935-rs16843804 or rs2857935-rs16843836 produced selective genomic deletions in mutant HTT and prevented the transcription of mutant HTT mRNA without impacting the expression of normal counterpart or re-integration of the excised fragment elsewhere in the genome. RNA-seq and off-target analysis confirmed high levels of allele specificity and the lack of recurrent off-targeting. Approximately 60% of HD subjects are eligible for mutant-specific CRISPR-Cas9 strategies of targeting one of these three PAS in conjunction with one non-allele-specific site, supporting high applicability of PAS-based allele-specific CRISPR approaches in the HD patient population. [Display omitted] CRISPR-Cas9 to selectively inactivate mutant huntingtin may produce robust therapeutic benefits in Huntington’s disease (HD). We revealed PAM-altering SNPs that permit allele-specific CRISPR-Cas9 in HD (rs2857935, rs16843804, and rs16843836). Targeting those sites in combinations using dual gRNAs prevented the transcription of mutant HTT mRNA without impacting the normal counterpart.